Gestational diabetes mellitus-universal versus selective screening - Hymavathi, Kaliki; Tadisetti, Surekha; Polisetty, Kavya; Gottipatti, Malini Devi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The prevalence of diabetes mellitus is increasing globally and Indian population is found to be ethnically in high risk group. Gestational diabetes mellitus (GDM) offers a unique and valuable opportunity for the development and implementation of clinical strategies for future prevention of diabetes. There is immense need for optimal screening strategies to spot out women with gestational diabetes. Methods: Prospective case study.1000 pregnant women were recruited into the study at an early gestational age (<20 weeks). They were broadly divided into two groups A (without risk factors) and B (with risk factors).The whole study population (both A and B) is subjected to oral glucose challenge test (OGCT) with the concept of Universal screening. Those with abnormal OGCT are subjected to Oral glucose tolerance test (OGTT).Women with abnormal GTT values are designated as having GDM. The results are analyzed. Results: 11.7% in group A and 25.4% in group B were found to have abnormal OGCT values and when they were subjected to OGTT 44.2% in group A and 45.8% in group B are detected to have abnormal OGTT values. 87.9% of GDM women were found to be in the age group 21-25 years in group A and in group B (59.5%) were of >26 years. labor outcome by caesarean section in GDM cases was up to 60% and 51.3% being elective sections. On the whole neonatal outcome was satisfactory. Conclusions: As Indian population are ethnically more prone for diabetes, there is immense need to adopt universal screening for GDM in pregnancy. Thus, a timely action can be taken as depicted in the present study by screening all pregnant women, irrespective of the presence/absence of risk factors.